Effects of nano-sized boron nitride on thermal decomposition and water resistance behaviour of epoxy-based intumescent coating - Ahmad, F. (Elsevier B.V., 2018)
In present research work, the effect of nano-sized boron nitride (BN) was studied on intumescent fire retardant coating (IFRC) for structural application. The coated steel substrates were subjected to furnace fire test at 800 Â°C for 2 h and fire protection test for 1 h. The coatings were characterized by Thermogravimetric analysis (TGA) while the char from fire test was characterized by field emission scanning electron microscopy (FESEM), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR) and X-ray photoelectron spectroscopy (XPS). Furnace fire test showed that IFRC reinforced with 4 mass of nano-sized BN expanded more than 54.84 compared to the BN-1 formulation. Fire protection test performed for 1 h showed minimum substrate temperature of 140 Â°C with 4 mass of BN which proved that the IFRC can successfully protect steel substrates within its critical temperature. A maximum of 44.49 residual mass was also recorded for the same coating. XRD analysis revealed that the remaining char contained boron phosphate, boron nitride and phosphoric nitride which are stable at high temperature. The presence of these compounds was also confirmed by functional group analysis using FTIR. FESEM confirmed that micrograph of char contained hexagonal BN. XPS analysis showed a fraction decrease in carbon contents of char residues of intumescent coating formulations with the increase of BN quantity. Pyrolysis GCâMS confirmed that formulations BN-4 released less gaseous product concentration compared to BN-1. Water immersion test showed that there was no trend of mass gain percentage with increasing amount of nano-sized boron nitride incorporated into the coating. The mass gain remained between 1.74 to 2.82. Overall concluded that the formulation with 4 mass BN effectively promoted the amount of char acted as a passive protective layer to the substrate resulting in lower substrate temperature with higher coating residual mass. Â© 2018 Elsevier B.V.